2017
DOI: 10.1016/j.aquatox.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Primary hepatocytes from Arctic char (Salvelinus alpinus) as a relevant Arctic in vitro model for screening contaminants and environmental extracts

Abstract: Contaminants find their way to the Arctic through long-range atmospheric transport, transport via ocean currents, and through increased anthropogenic activity. Some of the typical pollutants reaching the Arctic (PAHs, PCBs) are known to induce cytochrome P450 1a (CYP1A) protein expression and ethoxyresorufin-O-deethylase (EROD) activity through the aryl hydrocarbon receptor (AhR). In addition, some endocrine disrupting chemicals (EDCs) such as estrogen mimics (xenoestrogens) have been documented in Arctic area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…It was reported that benzopyrene had the potential to induce oxidative stress in primary grouper liver cells and the oxidative effects of benzopyrene were assessed as a potential toxicology research technique [4]. Fish liver cell lines were also widely used in vitro models to study the adverse effects of pollutants in the marine environment [40]. The use of a 3-D in vitro liver organoid culture system (spheroids) derived from rainbow trout was reported to measure the metabolism of pharmaceuticals using a substrate depletion assay.…”
Section: Fish Hepatocytesmentioning
confidence: 99%
“…It was reported that benzopyrene had the potential to induce oxidative stress in primary grouper liver cells and the oxidative effects of benzopyrene were assessed as a potential toxicology research technique [4]. Fish liver cell lines were also widely used in vitro models to study the adverse effects of pollutants in the marine environment [40]. The use of a 3-D in vitro liver organoid culture system (spheroids) derived from rainbow trout was reported to measure the metabolism of pharmaceuticals using a substrate depletion assay.…”
Section: Fish Hepatocytesmentioning
confidence: 99%
“…Arctic char were collected and terminated in November 2015 with a blow to the head and subjected to a two-step liver perfusion as described in Tollefsen et al (2003) with minor modifications for Arctic char as described in Petersen et al (2017). Blood was removed from the liver by perfusion with a calcium free buffer (NaCl 122 mM, KCl 4.8 mM, MgSO4 1.2 mM, Na2HPO4 11mM, NaH2PO4 3.3 mM, NaHCO3 3.7 mM, EGTA 26 µM, 0°C) at 5 ml/min for 10-15 min.…”
Section: Isolation Of Primary Hepatocytesmentioning
confidence: 99%
“…Expression of Vtg gene and protein in male and juvenile fish has therefore become a suitable biomarker for (xeno)estrogenic compound exposure (Heppell et al, 1995;Mommsen and Walsh, 1988;Purdom et al, 1994). Synthesis of Vtg has also been used as a biomarker in primary cultures of hepatocytes from temperate fish such as common bream (Abramis brama), Siberian sturgeon (Acipenser baeri), Japanese eel (Anguilla japonica), channel catfish (Ictalurus punctatus), common carp (cyprinus carpio), rainbow trout (Oncorhynchus mykiss), Mozambique tilapia (Oreochromis mossambicus) (reviewed by Navas and Segner, 2006), and Atlantic salmon (Salmo salar) (Tollefsen et al, 2003), and in the recently established multi-endpoint and highthroughput in vitro bioassay with Arctic char hepatocytes for screening single chemicals, complex mixtures, and environmental extracts (Petersen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Two-step collagenase perfusion was originally described by Berry and Friend [22] for the rat liver, but Birnbaum et al [23] adapted it for the fish liver as well [24]. The authors Baksi and Frazier [22] and Pesonen and Andersson [21] revised the properties and usage of fish primary cell cultures and, even now, a considerable number of studies are still reporting the application of these cultures as a good alternative for the replacement of aquatic organisms [14,19,[25][26][27][28][29]. However, most of these studies used freshwater species models, and there is a lack of information regarding the isolation and culture conditions for marine fish hepatocytes.…”
Section: Introductionmentioning
confidence: 99%